ANALISIS KESALAHAN SISWA DALAM MENGERJAKAN SOAL FUNGSI INVERS PADA KELAS XI DI SMA TEKNOLOGI KOTA SORONG: ANALYSIS OF STUDENTS' ERRORS IN WORKING ON INVERSION FUNCTION PROBLEMS IN GRADE XI AT SORONG CITY TECHNOLOGY HIGH SCHOOL - Andini, Rya; Mahendra, Faisal Eka; Budiarti, Marlinda Indah Eka (KAMBIK: Journal of Mathematics Education, 2024)
This study aims to analyze the errors made by Grade XI students of SMA Teknologi Kota Sorong in solving inverse function problems and to identify the factors causing these errors. The approach used is qualitative with a descriptive method, where data were obtained through diagnostic essay tests and observations of 15 students. The analysis results show that students' errors fall into four main categories: conceptual errors at 7%, principal errors at 7%, factual errors, which dominate with a percentage of 47%, and operational errors at 20%. A total of 20% of students were able to answer all questions correctly. The primary causes of errors include a lack of understanding of the basic concept of inverse functions, improper application of formulas, and inaccuracy during calculations. External factors such as ineffective teaching methods and low student motivation further exacerbate the level of errors that occur. This study provides important contributions to the development of more effective learning strategies, helping teachers create a more meaningful mathematics learning process that focuses on students' comprehensive understanding.